2003
DOI: 10.1093/her/18.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of HIV infection: how do women decide to tell?

Abstract: This descriptive study explores the phenomenon of disclosure of HIV infection by women. Specifically, we examined women's level of disclosure to various groups and how these disclosure decisions are made. The sample consisted of 322 HIV-infected women residing in the southern US. Participants were predominantly African-American, single women of reproductive age with yearly incomes less than $10,000. Data were collected at the first interview of a longitudinal study of reproductive decision making. Findings sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 29 publications
5
69
0
1
Order By: Relevance
“…In four of these five cases, the primary motivation for disclosure was based on educating others about HIV from both social and biological perspectives. This is consistent with a study of 322 HIV-positive African-American women, where content analysis highlighted motivations that included a desire to increase awareness around HIV/AIDS and to overcome AIDS-related stigma through disclosure of their HIV-status to significant others (Sowell et al, 2003). Similarly, in a qualitative study in two South African communities, Norman et al (2005) found that that disclosure was used as an opportunity to educate significant others and challenge HIV/AIDS stigma.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In four of these five cases, the primary motivation for disclosure was based on educating others about HIV from both social and biological perspectives. This is consistent with a study of 322 HIV-positive African-American women, where content analysis highlighted motivations that included a desire to increase awareness around HIV/AIDS and to overcome AIDS-related stigma through disclosure of their HIV-status to significant others (Sowell et al, 2003). Similarly, in a qualitative study in two South African communities, Norman et al (2005) found that that disclosure was used as an opportunity to educate significant others and challenge HIV/AIDS stigma.…”
Section: Discussionsupporting
confidence: 74%
“…More recently, studies have also been conducted amongst immigrant populations (Sowell et al, 2003;O'Brien et al, 2003) as HIV infections are increasing. There is also a small emerging literature on disclosure in developing countries (see Medley et al, 2004) and in South Africa (Soskolne et al, 2004;Kahn, 2004, Matthews et al, 1999Norman et al 2005;Almeleh, 2004;Brandt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption might not hold, as several studies, both qualitative and quantitative, indicate that each act of disclosure to a particular type of actor may have different causes and consequences. For example, disclosure to a partner may be intended to prevent HIV transmission and to gain social support in the context of a steady relationship, disclosing to a family member may aim for emotional or financial support, while disclosing to a broader audience may be motivated by a wish to change the perception of PLWH by the community at large (Greeff et al, 2008;Sowell et al, 2003;Stutterheim, Shiripinda et al, 2011;Vu et al, 2012). Hence, other authors chose to analyze disclosure acts to different actor categories separately (Armistead et al, 1999;Tsai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For the majority of individuals with HIV, disclosure is stressful. There is a fear of rejection, discrimination, and abandonment (Sowell, Seals, Phillips, & Julious, 2003;Levy et al, 1999). Rather than the relief that is anticipated when one discloses to other, there are often regrets (Levy et al, 1999).…”
mentioning
confidence: 99%
“…Other steps in the process include evaluating one's personal disclosure skills, deciding whom to tell, considering the recipient's circumstances, anticipating the recipient's reaction, and having a motivation to disclose. HIV infected individuals consider specific criteria of the recipient including not only their relationship to the person, but also the quality of that relationship, as well the perceived likelihood that the other person will keep the information confidential (Sowell, Seals, Phillips, & Julious, 2003). While disclosure is usually a reasoned decision, it also can be an emotion outburst (Levy, et al, 1999).…”
mentioning
confidence: 99%